2020
DOI: 10.1136/sextrans-2019-054248
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting first-time hepatitis C virus testing uptake among men who have sex with men in China: an observational prospective cohort study

Abstract: ObjectivesMen who have sex with men (MSM) are at high risk of hepatitis C virus (HCV). This study investigated predictors of first-time HCV testing uptake during a 6-month period among a sample of MSM in Hong Kong.MethodsParticipants were 351 Chinese-speaking MSM who had never received HCV testing. Participants completed two telephone surveys 6 months apart. At baseline, participants reported on sociodemographics, sexual behaviours, risk perception, depressive symptoms and anxiety symptoms. Illness representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Our data suggest a low HCV test uptake among the general population. This is consistent with data from among men who had sex with men (MSM) who had never tested for HCV infection 28 but lower than the 41% uptake rate found among MSM in a recent…”
Section: Discussionsupporting
confidence: 90%
“…Our data suggest a low HCV test uptake among the general population. This is consistent with data from among men who had sex with men (MSM) who had never tested for HCV infection 28 but lower than the 41% uptake rate found among MSM in a recent…”
Section: Discussionsupporting
confidence: 90%
“…The dimension of treatment control was associated with both PV uptake among all participants and behavioral intention to take up PV among unvaccinated aging adults. In general, treatment control is significantly associated with uptake of seasonal influenza vaccination, 24 hepatitis C virus testing, 27 and treatment adherence to some chronic diseases (e.g., asthma, hypertension). 29 Beliefs in treatment control of pneumonia may be related to perceived efficacy of PV, which has shown to be significantly associated with behaviors and intentions related to PV.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional representations are defined as the extent to which individuals are emotionally affected by the illness (e.g., feeling anger, guilt, or shame). 23 This concept has also been expanded to explain health behaviors among healthy individuals, including uptake of influenza vaccination, [24][25][26] hepatitis C virus testing, 27 cancer screening, 28 and self-care practices for chronic diseases. 29,30 There is a dearth of studies investigating illness representations on pneumonia and association with PV uptake, a potential coping response.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have revealed that illness perception impacts coping behavior of individuals which is linked to their health-related outcomes [ 9 11 ]. Coping behaviours or strategies are behavioral and cognitive strategies adopted by individuals to manage stress associated with having to live with the disease (e.g., adapting certain kind of physical activity or actively diverting attention from the illness) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Langston et al [ 10 ] reported that positive illness perception has successfully improved the mental health condition and lowered the substance abuse in individuals with HCV. On the contrary, Wang et al [ 11 ] and Nergiz et al [ 31 ] associated poor HCV perception of individuals with their negative emotions and anxiety.…”
Section: Introductionmentioning
confidence: 99%